FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA ANEMIA PADA IBU HAMIL DI PUSKESMAS COT IE JUE KECAMATAN PEUSANGAN KABUPATEN BIREUEN TAHUN 2023 - Sari, Nur Mala; Husna, Fadhlinal (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Pregnancy-related anemia is a widespread issue because it has a significant impact on the quality of human resources and reflects the socioeconomic status of the community. Pregnant women's anemia is considered